KADO SPESIAL: Strategic Innovation for Conservation Area Management in Pieh Island National Marine Protected Area, West Sumatra - Rahmat Irfansyah; Muh. Firdaus Agung Kunto Kurniawan; R. Hernan Mahardhika; Fajar Nugroho; Dominikus Yoeli Wilson Laia (Center for Maritime Policy and Governance Studies. Universitas Maritim Raja Ali Haji. Indonesia, 2024)
The Pieh Island National Marine Protected Area (NMPA) is managed by the LKKPN (National Marine Protected Area Office) Pekanbaru and includes distinct zones: a 197.34-hectare core zone, a 39,681.1-hectare limited utilization zone, and a 41.56-hectare anchoring and habitat rehabilitation zone. The largest, the limited utilization zone, highlights the importance of managing human interactions within the MPA. This research focuses on identifying and exploring strategies to address challenges faced by LKKPN Pekanbaru in managing the Pieh Island NMPA, specifically using the Bando Island area as a case study. Bando Island, a survival tourism destination within the MPA, needs to be more adequately managed. A literature review and data collection through focus group discussions (FGD) were conducted. Issues were explored and validated using the APKL (Aktual, Problematik, Khalayak, Layak) analysis, with priorities determined by the USG (Urgency, Seriousness, Growth) matrix. Fishbone analysis was used to identify root causes of top-priority issues, and alternative strategies were ranked using the McNamara approach. The research identified the lack of stakeholder collaboration as the primary issue, leading to the development of the